COMPARISON OF THE STEP EXERCISE METHOD FOR RESTING PULSES AND RECOVERY PULSE RATES IN TBM FKIK WARMADEWA - Tanjung Subrata; Ni Wayan Rusni; Luh Gede Pradnyawati (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Being a member of the Tim Bantuan Medis (TBM) is required not only to have excellent health but also to have optimal physical fitness, bearing in mind that Indonesia is a disaster-prone area where disasters can occur anytime and anywhere. The research was conducted on members of the TBM of Fakultas Kedokteran dan Ilmu Kesehatan (FKIK) Warmadewa, aiming to compare the step exercise (SE) method to the resting pulse rate and recovery pulse rate in TBM students. The research was conducted at the Physiology Laboratory of FKIK Warmadewa, with ethical clearance Number: 323/Unwar/FKIK/EC-KEPK/IV/2023. This study used 71 samples of TBM students who were divided into 3 groups using a simple random method. P1 group did SE at a frequency of 100 x/minute for 216 seconds, group P2 did SE at a frequency of 110 x/minute for 196 seconds, group P3 did SE at a frequency of 120 x/minute for 180 seconds, exercises were carried out 3 times per week, during 4 weeks. All subjects were tested for cardiorespiratory fitness with the Harvard Step Test and compared the pre and post exercise results. Data analysis was performed using the paired t test method to see a comparison of the step exercise method on resting pulse and recovery pulse rate. The results showed that at P1 and P3 there was no significant decrease in the pre-post resting pulse (p>0.05), whereas in the recovery pulse there was a significant decrease (p